Decentralizing security architecture: evaluating federalism’s role in enhancing security frameworks in Nigeria (Law and Safety, 2024)
This study delves into the intricate security landscape of Nigeria, a nation grappling with a myriad of challenges such as terrorism, insurgency, banditry, and communal conflicts. The existing centralized security architecture has been found wanting in its ability to effectively mitigates these threats and safeguards the well-being of Nigerian citizens. To gain a deeper understanding of these issues, the study employs a well-structured questionnaire as its primary data collection tool and utilizes a descriptive analytical model as its theoretical framework. It leverages descriptive quantitative tools to scrutinize the collected data, aiming to provide a logical interpretation of the situation. The study identifies lack of decentralization in the security architecture and skewed federalism as key contributing factors to the prevailing insecurity in Nigeria. It uncovers a multitude of causal variables that contribute to the internal insecurity in the country. A significant finding of the study is the correlation between the over-centralization of the security architecture and the rising insecurity across the nation. It posits that the higher the level of centralization, the greater the alienation of citizens in the security of their local areas. In light of these findings, the study advocates for Nigeria to embrace the principles of true federalism. It recommends amendments to the 1999 constitution, suggesting that the majority of the items currently in the exclusive lists should be moved to the concurrent lists. This would pave the way for regional integration and the establishment of regional security outfits, such as the Amotekun in the south west, thereby fostering a more secure and harmonious nation.
Keywords: decentralisation; federalism; security; architecture; security frameworks.